2018
DOI: 10.3390/rs10121972
|View full text |Cite
|
Sign up to set email alerts
|

Remotely Sensed Single Tree Data Enable the Determination of Habitat Thresholds for the Three-Toed Woodpecker (Picoides tridactylus)

Abstract: Forest biodiversity conservation requires precise, area-wide information on the abundance and distribution of key habitat structures at multiple spatial scales. We combined airborne laser scanning (ALS) data with color-infrared (CIR) aerial imagery for identifying individual tree characteristics and quantifying multi-scale habitat requirements using the example of the three-toed woodpecker (Picoides tridactylus) (TTW) in the Bavarian Forest National Park (Germany). This bird, a keystone species of boreal and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 80 publications
1
21
0
1
Order By: Relevance
“…It is known that gaps are related to forest biodiversity [63] and the size influences forest dwelling species, for instance ants [64] which are in turn related to TreMs. In addition remote sensing techniques have been used to detect habitat thresholds for indicator species as the three-toed woodpecker (Picoides tridactylus) based on canopy properties such as the amount of deadwood crown size [19], which will eventually result in canopy gaps and points in a similar direction as our results. Therefore, we could suggest to focus selection activities of habitat trees to forest areas with a certain degree of gaps in the canopy.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is known that gaps are related to forest biodiversity [63] and the size influences forest dwelling species, for instance ants [64] which are in turn related to TreMs. In addition remote sensing techniques have been used to detect habitat thresholds for indicator species as the three-toed woodpecker (Picoides tridactylus) based on canopy properties such as the amount of deadwood crown size [19], which will eventually result in canopy gaps and points in a similar direction as our results. Therefore, we could suggest to focus selection activities of habitat trees to forest areas with a certain degree of gaps in the canopy.…”
Section: Discussionsupporting
confidence: 56%
“…The remote sensing (RS) discipline mainly describes forest structure by summarizing variables that can 2 of 20 be determined from sensor data. These include maximum height, quantiles of height from surface models or point clouds, point densities, or structural complexity indices, tree counts, biomass estimates and many more [3,[13][14][15][16][17][18][19][20][21][22][23][24][25][26]. If the aim is to provide a broader perspective of the forest structure, metrics such as the Stand Structural Complexity Index (SSCI) [4] are for instance applicable.…”
Section: Introductionmentioning
confidence: 99%
“…The main objectives and the novelties of the current study were (i) to optimise tree segmentation based on normalized cut using two different stopping criteria for conifers and broadleaf trees and (ii) to map conifers, broadleaf trees, standing dead trees, and snags in a large temperate forest 924 km 2 in size situated in Šumava National Park and Bavarian Forest National Park. Thereby, we verified the statistical performance of the methods in a large-scale experiment and provided spatial information about the distribution of trees usable for area-wide information on the abundance and distribution of key habitat structures [28].…”
Section: Introductionmentioning
confidence: 82%
“…Tree deaths are significant in a circular ecology, since they provide resources to many organisms [1] and habitat to many mammals and birds [2]. Zielewska-Büttner et al [3] showed that the abundance of dead standing trees (snags) was the most important predictor of woodpecker habitat sections, stressing this way the importance of dead wood. At the same time, decaying wood is decreased at managed forests and this is a thread for organisms whose lives depends on dead wood [4].…”
Section: Introductionmentioning
confidence: 99%